2019
DOI: 10.1002/bjs.11139
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of patient-reported outcomes after laparoscopic versus open inguinal hernia repair

Abstract: Background: Inguinal hernia repair is a common low-risk intervention. Patient-reported outcomes (PROs) are being used increasingly as primary outcomes in clinical trials. The aim of this study was to review and meta-analyse the PROs in RCTs comparing laparoscopic versus open inguinal hernia repair techniques in adult patients.Methods: A systematic review and meta-analysis was carried out in accordance with PRISMA guidelines. Only RCTs in peer-reviewed journals were considered. PubMed, Ovid Embase, Scopus and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 71 publications
(246 reference statements)
1
16
0
1
Order By: Relevance
“…At present, the treatment of CPSP is not optimistic. In addition to drug therapy (37), some case reports suggest the use novel ultrasound-guided blocks in the management of CPSP can obtain satisfactory results. In a pilot study following breast surgery, the authors investigated the analgesic effect of an ultrasound-guided pectoral nerve block with 20 mL of bupivacaine 0.25%.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the treatment of CPSP is not optimistic. In addition to drug therapy (37), some case reports suggest the use novel ultrasound-guided blocks in the management of CPSP can obtain satisfactory results. In a pilot study following breast surgery, the authors investigated the analgesic effect of an ultrasound-guided pectoral nerve block with 20 mL of bupivacaine 0.25%.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery is the standard procedure for inguinal hernia repair and its advantages include a good view of the surgical field, reduction in wound pain, and, the most remarkable aspect, easy observation, diagnosis, and repair of subclinical and contralateral groin hernias 15‐17 . In this case, three additional hernias that could not be detected preoperatively were successfully detected during laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 79%
“…It has been reported that laparoscopic hernia repair results in not only significantly less early and late postoperative pain but also better patient‐reported satisfaction compared with open hernia repairs 5 . However, in the early days of laparoscopic inguinal hernia repair, postoperative neuralgia due to intraoperative nerve injury occurred occasionally and was the most serious problem following TAPP 1 .…”
Section: Discussionmentioning
confidence: 99%